Temporal characteristic of the scanner influencing dosimetry using radiochromic film. (September 2016) - Gotanda, T.; Katsuda, T.; Gotanda, R.; Akagawa, T.; Tanki, N.; Kuwano, T.; Kawaji, Y.; Shimono, T.; Fukuda, K.; Mizumoto, T.
Abstract : Introduction: Recently developed radiochromic films can easily measure the absorbed doses by using a flat-bed scanner. However, in a GAFCHROMIC EBT3 (EBT3) radiochromic film, the precision of the measurement was compromised because of the change in density caused by the scan timing of image acquisition using a flat-bed scanner. Purpose: The purpose of this study was to investigate the temporal light source change of a flat-bed scanner affecting the density of EBT3. Materials and methods: EBT3 without irradiation was used to remove non-uniformity error caused by irradiation. EBT3 was scanned every hour (0–6 h) from power activation to investigate the temporal light source change of a flat-bed scanner (EPSON ES-10000G). In addition, five consecutive scans were performed every hour. Scan parameters were RGB (48 bit) mode, 100 dpi, the reflection mode. Image data of EBT3 was divided into R, G, and B modes, and the R (16 bit) mode was used. The region of interest has a diameter of 75 pixels in the center of the EBT3 sheet. Results: The density gradually decreases after power activation and became the plateau 5 h later. After the first scan, a low density is observed: the density was stable after the third scan. Conclusion: To improve repeatability of EBT3, the scan must be performed only after 5 h power activation. In addition, the image data obtained after the third consecutive scan must be used. Disclosure: We have no disclosure and financial support.